THE EFFECT OF ZAKAT ON POVERTY REDUCTION IN RIAU PROVINCE - Agustin, Hafizah (Fakultas Studi Islam Universitas Muhammadiyah Riau, 2023)
This research aims to examine the effect of Zakat on poverty reduction in Riau Province. The research method used was quantitative. The data used in this research was secondary data obtained in the form that already exists and was collected and processed by other parties in the form of financial reports on the distribution of Zakat funds at district/city BAZNAS for the period 2017 to 2021 recorded at BAZNAS Riau Province and the number of poor people in districts/cities which are recorded in the Central Statistics Agency of Riau Province. The data analysis method used panel data regression with the research model, namely Fixed Effect using the help of E-Views version 12 software. The results show that Zakat funds have a significant effect in reducing the number of poor people in Riau Province. It can be concluded that Zakat funds collected by BAZNAS are well distributed. Where it can be seen from the 5 (five) excellent programs in BAZNAS, namely the fields of economy, education, humanity, health and religion. So that zakat funds distributed through the five programs can affect poverty reduction in Riau Province. Keywords : Distribution, Poverty Level, Zakat